The effect of carbodiimide on push-out bond strength of fiber posts and endogenous enzymatic activity - Uros Josic; Claudia Mazzitelli; Tatjana Maravic; Allegra Comba; Milena Cadenaro; Ivana Radovic; Maicon Sebold; Gianluca Turco; Lorenzo Breschi; Annalisa Mazzoni (BMC, 2023)
Abstract Background To investigate the effect of 0.3 M 1-ethyl-3(3-dimethylaminopropyl) carbodiimide (EDC) aqueous solution pretreatment on push-out bond strength (PBS) and matrix-metalloproteinases (MMPs) activity within radicular dentin when different post cementation strategies were employed. Methods One hundred and twenty monoradicular human teeth were endodontically treated and randomly divided into six groups, depending on the cementation strategy and root dentin pretreatment (n = 20): EAR: cementation with an etch-and-rinse adhesive (LuxaBond Total Etch, DMG) and resin cement (LuxaCore Z Dual, DMG); EAR/EDC: 1 min EDC pretreatment after etching + EAR; SE: cementation with a self-etch primer (Multilink Primer, Ivoclar Vivadent) and corresponding cement (Multilink Automix, Ivoclar Vivadent); SE/EDC: self-etch primer + EDC pretreatment + SE; SA: cementation with a universal self-adhesive cement (RelyX Universal, 3 M); SA/EDC: EDC pretreatment + SA. Slices were submitted to PBS test and interfacial nanoleakage evaluation 24 h after cementation or after thermocycling (40.000 cycles, 5-55 °C). To investigate the effect of EDC on MMPs activity, 4 additional first maxillary premolars per group were processed for in situ zymography analysis. Multivariate ANOVA and post hoc Tukey tests were used to analyze PBS values. The data from in situ zymography were analyzed with Kruskal-Wallis test and Dunn's pairwise multiple comparison procedures (α = 0.05). Results The variables "EDC pretreatment", "root region" and "thermocycling" significantly influenced PBS (p < 0.05), while the variable "cementation strategy" had no influence (p > 0.05). Thermocycling significantly reduced PBS in SE and SA groups (p < 0.05). EDC was effective in preserving PBS after artificial aging. EDC pretreatment significantly reduced enzymatic activity at baseline in EAR and SE groups, and in SA group after thermocycling (p < 0.05). Conclusions The use of EDC prevents the reduction of bond-strength values after artificial aging and silences endogenous enzymatic activity within radicular dentin when different cementation strategies were employed.